WordStar for DOS - Ettlin,Walter A. (WordStar International, 1992)
Word processing program that allows the user to view page layout before printing, import fax files in twenty-three formats and graphics in twenty-seven formats, convert files to/from popular word processors, and import database and spreadsheet files. Includes macros, mail-merge, text editing, and support for laser and PostScript printers.